MENSTRUAL PERIOD ANALISIS OF WOMEN PLWHA WITH ANTI RETROVIRAL THERAPY (ART) IN NGO LANCANG KUNING PEKANBARU CITY - Martilova, Dona; Amran, Husna Farianti (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2017)
Acquired Immunodeficiency Syndrome (AIDS) is caused by Human Immunodeficiency Virus (HIV), including infectious diseases that cause weakness of the immune system. Riau province on the 11st grade of most cases of AIDS that is 1104 cases and 53% occur in women. Treatment that can be done is to use antiretroviral therapy (ART). ARV drugs do not kill the virus but can slow the growth of the virus. The use of antiretroviral drugs can cause side effects in some women the use of antiretroviral drugs causes menstrual disorders such as prolonged bleeding, menstrual bleeding time, faster menstrual periods, longer menstrual intervals, and, periods sometimes do not occur.The research type is quantitative with cross sectional approach. The study was conducted from May to December 2017. The study population was all women living with HIV / AIDS under the guidance of NGO Lancang Kuning Pekanbaru which amounted to 96 people with a sample of 53 people taken with Simple Random Sampling technique (simple random), Instrument data collection is a questionnaire in the form of a list question and checklist list. Data were analyzed by Univariate to know the frequency distribution of respondent, and Bivariate (chi-square) to know the relation between variables. The results showed that menstrual cycle disorders in HIV-positive women were associated with age (P value 0.001), duration of use of antiretroviral therapy (P value 0.004), nutritional status of women living with HIV (P value 0,003) and environmental factor (P value 0,000). It is recommended that women living with HIV / AIDS can take Anti retroviral medication regularly and maintain their nutritional status in good condition and it is expected that the environment can provide support to PLHIV women.